Perancangan dan Implementasi Sitem Coding Bill of Material (COM) Sebagai Pendukukung Pengelolaan Produk di PT XYZ - Vira Agustin Nursalisa; Syahla Fadya Ayuditha; Fahla Septiani Tanjung; Zain Hauzan Musyaffa (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This research focuses on designing an integrated Bill of Material (BOM) coding system to optimize product data management at PT XYZ. The primary problem addressed is the lack of standardized codification, which triggers product identification errors by operators and creates information silos between departments. By integrating the Design Thinking method and the IISE 14 Body of Knowledge standards, this study developed a web-based information system prototype. The utilization of technical diagrams such as Use Case, Activity Diagram, DFD, and ERD ensures that the product information flow becomes more transparent and accessible in real-time across all departments, from PPIC to Quality Control.